Business Ethics Quarterly (Cambridge)
Business Ethics Quarterly (BEQ) is a peer-reviewed scholarly journal which publishes theoretical and empirical research relevant to the ethics of business, corporate social responsibility, and corporate sustainability. Recognizing that contributions to the better understanding of these topics can come from any quarter, and that the best scholarship on these themes is often interdisciplinary in nature, it publishes scholarship from the humanities, social sciences, and professional fields, as well as scholarship that crosses disciplinary boundaries.
Keywords: Philosophy